PROMOTING STUDENTS’ SPEAKING SPONTANEOUS THROUGH ENGLISH SURVIVAL ACTIVITY: A CASE STUDY ON STUDENTS OF AGRICULTURE - Eka Nurhidayat; Eva Fitriani Syarifah (Universitas PGRI Semarang, 2022)
English lecturers frequently worry about encouraging students to use English in spontaneous conversation, mainly English, for specified purposes. The study details classroom activities that encourage students to talk spontaneously in Agriculture. An early stage of group preparation is required to instil confidence in students to speak English freely in class. Students are responsible for identifying themes and laying the framework for class discussions. Cultivation, food production, and cattle business are suggested materials for various class activities. The teacher's role is to enlighten students about available resources, establish ground rules, and promote free expression. These events are intended to instil students’ confidence in English speaking.